Phase 2 randomized study of bortezomib-melphalan-prednisone with or without siltuximab (anti–IL-6) in multiple myeloma - San-Miguel, Jesús (American Society of Hematology, 2014)
Because interleukin-6 (IL-6) is considered important in the proliferation of early multiple myeloma (MM), we hypothesized that the addition of the anti-IL-6 monoclonal antibody siltuximab to the bortezomib-melphalan-prednisone (VMP) regimen would improve outcomes in transplant-ineligible patients with newly diagnosed MM. One hundred and six patients were randomized to receive 9 cycles of VMP or VMP plus siltuximab (11 mg/kg every 3 weeks) followed by siltuximab maintenance. Baseline characteristics were well balanced except for immunoglobulin A subtype and 17p deletions. With a complete response (CR) rate of 27% on siltuximab plus VMP (S+VMP) and 22% on VMP, the study did not confirm its hypothesis that the addition of siltuximab would increase the CR rate by at least 10%. Overall response rate was 88% on S+VMP and 80% on VMP, and at least very good partial response rates were 71% and 51% (P = .0382), respectively. Median progression-free survival (17 months) and 1-year overall survival (88%) were identical in the 2 arms. Grade ≥3 adverse-event incidence was 92% on S+VMP and 81% on VMP (P = .09), with trends toward more hematologic events and infections on S+VMP. Maintenance therapy with siltuximab was well tolerated. In conclusion, the addition of siltuximab to VMP did not improve the CR rate or long-term outcomes. This study was registered at http://clinicaltrials.gov as #NCT00911859.